The Relationship Between Nurse Performance in Providing Nursing Care and Patient Satisfaction at Budhi Asih General Hospital Jakarta - Muhammad Reza Fahlevi Hanafi; Harif Fadhillah; Giri Widagdo; Rayahu Nawangwulan (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2025)
Background: Patient satisfaction reflects patients’ perceptions and needs regarding the utilization of healthcare services. Nurse performance in Indonesia has been reported to be relatively low (53.4%). Objectives: To examine the relationship between nurse performance in providing nursing care and patient satisfaction at Budhi Asih General Hospital, Jakarta. Methods: This study employed a descriptive correlational design with a sample of 173 respondents determined using Lameshow’s proportion formula. Data were analyzed using logistic regression. Results: The study found that nurse performance was significantly associated with patient satisfaction (p-value 0.03 < 0.05). Multivariate analysis confirmed that nurse performance remained significantly related to patient satisfaction. Conclusion: Nurse performance had an odds ratio (OR) of 4.5 (95% CI: 1.926–10.877), indicating that nurses’ performance increases the likelihood of patient satisfaction fourfold after controlling for age, marital status, and length ofstay.